Spontaneous Resolution of Cystic Adventitial Disease of the Popliteal Artery - Georges Ibrahim; Sami Nabhani; Michel Feghaly; Georges Baaklini (Case Reports in Vascular Medicine)
Spontaneous resolution of cystic adventitial disease (CAD) is rare with occasional reports in the literature. In this case report, we are describing a 30-year-old man who presented with rapid onset of severe intermittent claudication and was diagnosed with CAD. Resection of the lesion with autologous vein replacement was scheduled. However, the claudication suddenly improved at 4 weeks after onset. Ultrasonography and computed tomography revealed regression of the cystic lesions with resolution of the popliteal artery stenosis. His symptoms did not recur during the 12-month follow-up period. Although it is unclear whether this resolution is permanent, in this report, we describe our experience with a case of CAD that eventually spontaneously regressed and the possibility of conservative treatment.